Molecular identification of Entamoeba histolytica from stool samples of Ilam, Iran. (April 2019) - Najafi, Azar; Mirzaei, Asad; kermanjani, Ali; Abdi, Jahangir; Ghaderi, Abolhassan; Naserifar, Razi
Highlights: Amoebiasis is a multifactorial, life-threatening public health issue and the third parasitic disease cause of mortality in worldwide. The aim of this study use of CP8 gene for differentiation between Entamoeba histolytica and Entamoeba dispar in its various infectious properties isolated from Iran. It is concluded that PCR is highly sensitive to detect E. histolytica and indicating this important role as screening tools in direct DNA extraction from stool samples and valuable technique in early detection of symptomatic and asymptomatic E. histolytica patients. Methods to get closer to a gold standard test and reduce treatment costs. This study would open new doors towards the complicated biology and pathogenesis of Amoebiasis infection, emphasizing the more detailed focus on this protozoan parasite. Abstract: Introduction: Amoebiasis is a multifactorial, life-threatening public health issue and the third parasitic disease cause of mortality in worldwide, particularly in low- and mid-income countries. The aim of this study was to attempt to explore genetic encoding differences of CP8 (conserved gene) of Entamoeba histolytica/Entamoeba dispar in its various infectious properties isolated from Ilam located at a southwest part of Iran. Materials and methods: A total of 2023 stool samples were collected between 2016 and 2018 from the hospital in Ilam, of which only 30 isolates were identified as E. histolytica/E. dispar . These isolates were collected from the intensive care unit, infectious disease, and surgery settings. The isolates were identified and the polymerase chain reaction (PCR) was performed to detect the CP8 gene. In all stages, Entamoeba histolytica HM1: IMSS was used as a positive control. Results: In genotype confirmation, only two isolates had the CP8 gene found in the PCR technique. The sequencing results confirmed the mentioned gene with 99%–100% specificity. Conclusion: It is concluded that PCR is highly sensitive to detect E. histolytica and indicating this important role as screening tools in direct DNA extraction from stool samples and valuable technique in early detection of symptomatic and asymptomatic E. histolytica patients.